ANALISIS PENINGKATAN DERMAGA PADA PT BERLIAN MANYAR SEJAHTERA SURABAYA - Ahmad Supriyatna; Sahat Martua Sihombing; Achmad Pahrul Rodji (Fakultas Teknik Universitas Krisnadwipayana, 2022)
The fender functions as a cushion that is placed in front of the pier, so that the fender can withstand the pierstructure from impact when the ship is maneuvering to lean on the pier. Ships docked at the pier still have speedeither driven by their own engines or pulled by tugboats. To avoid damage to ships and docks due to collisions, abearing or fender is installed in front of the dock which functions to absorb the impact energy. The amount ofimpact energy caused by the ship docking to the dock can be obtained by determining the block coefficient on theship, the ship mass coefficient, the ship's eccentricity coefficient to the dock, and the ship's docking speed in aperpendicular direction. The force transmitted to the pier depends on the type of fender and the allowabledeflection of the fender. When the ship hits the fender, the fender will deflect and transmit the impact force to thepier structure. Fender planning is determined based on the energy absorbed due to ship collision. The purpose ofthis study is to find out how to calculate the size of the pier required for one ship loading and unloading at thePort of PT. Berlian Manyar Sejahtear; knowing the size and strength of the required number of fenders at thePort of PT. Berlian Manyar Sejahtera; find out the number of fenders that will be used in upgrading the PT.Berlian Manyar Sejahtera. The research stages or steps of the research methodology begin with conducting a preliminary study or literature which includes literature study and data identification. The existing length of thepier is 200 meters, it will be increased by 50 meters so that the total length of the pier is 250 meters. The resultsof the analysis using 2 examples of ships docked at the PT. Berlian Manyar Sejahtera The length of the pier neededto serve the ships that dock is 226.8 meters. In the planning of PT. Berlian Manyar Sejahtera uses 1200 SCH or1200 SPC cone type fenders with an impact energy of 0.62 tm. The results of the analysis used a 1300 SPC conetype fender with an impact energy of 0.68 tm. Cone type fenders have a